(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Education is fundamental and important unit of society which place significant role in the development of society its helps in the development and progress of society and through various agencies like institution assumes greater importance by the way of providing quality to education received by the individual. The education received by the individual assume different roles in the way of performing various jobs, thus contributing for the good and progress of the society. When this is achieved on a larger scale its results in the development and progress of humanities and society. In this way education contributes enormously for the development of humanities.